Pengembangan Instrumen Motivasi Belajar Siswa: Kuesioner - Suhudi, Suhudi; Radeswandri, Radeswandri; Herlinda, Herlinda; Vebrianto, Rian (Jurnal Gentala Pendidikan Dasar, 2024)
The research instrument is an important factor in every study because it determines the accuracy of the research results which determines the conclusions. This tool is used to collect data and measure the object of a research variable. This research aims to re-test instruments related to learning motivation in the Natural Science lesson content for class V SDIT BPMAA Pekanbaru City which are valid and reliable which were previously developed by Aminatun, 2019. In the research These indicators of student learning motivation used are: (1) Perseverance in learning, (2) Tenacity in facing difficulties, (3) Interest and sharp attention in learning, (4) Achievement in learning, and (5) Independence in learning. This research involved 25 student respondents who were selected using purposive sampling technique. Data were analyzed using SPSS version 23.00 for Windows. The results of the research show that the obtained rcount moves from 0.614-0.762 and < rtable = 0.396 with a significance level of 5%. So that the statement items of the student learning motivation instrument are declared valid. Then the calculation results show that the reliability of the student learning motivation instrument is 0.601 with a total of N=25 (number of respondents) of 0.60, resulting in a superior and high quality instrument. This instrument is suitable to be used to measure what should be used to measure and evaluate student learning motivation effectively.